Post-traumatic epilepsy in children: developmental predictors and treatment strategy - D. S. Kanshina; T. A. Akhadov; I. A. Mel'nikov; G. A. Manushakyan; V. P. Zykov (Эпилепсия и пароксизмальные состояния)
Background. Post-traumatic epilepsy (PTE) in children is a significant medical and social problem affecting the quality of patients’ life. The periods of early and late convulsive seizures (CS) with a distinct pathophysiological basis are distinguished in the development of the disease. Pharmacoresistance formed due to structurally determined epileptogenic zones in PTE creates prerequisites for increasing the frequency of surgical interventions as the only effective treatment method to achieve seizure freedom.Objective: To analyze literature data on predictors of PTE development in children, efficacy of conservative and surgical treatment. Material and methods. In accordance with the PRISMA approach, 29 foreign and Russian publications found in PubMed/ MEDLINE and eLibrary databases and published between 2014 and 2024 were selected for the review, including 7 systematic reviews and meta-analyses. The selection criterion was the relevance of the publication topic to the search query “posttraumatic epilepsy in children”.Results. According to current concepts, there are four research areas assessing potential risks of PTE development in moderate and severe traumatic brain injury among children: biomarkers, genetic predisposition, neuroimaging and neurophysiological predictors. No justified therapeutic option for preventing early СS is available, while some studies have reported the efficacy of prophylactically used antiepileptic drugs to control incidence of late CS in the pediatric PTE population. PTE as a structural form of epilepsy has a high potential for the use of surgical therapies to achieve seizure freedom.Conclusion. The data analysis demonstrates the expansion of the clinical diagnostic approach in identifying risk factors for PTE in children, as well as shapes the understanding of the feasibility and efficacy of conservative and surgical treatments.